Decoding disclosure: Comparing conflict of interest policy among the United States, France, and Australia. Issue 5 (May 2018) - Grundy, Quinn; Habibi, Roojin; Shnier, Adrienne; Mayes, Christopher; Lipworth, Wendy
Highlights: "Sunshine" policies in the United States, France and Australia are compared. Transparency was proposed as a policy solution to several different problems. Disclosure makes assumptions about markets and leaves power relations unaddressed. Policymakers should use transparency data to begin to address industry influence. Abstract: "Sunshine" policy, aimed at making financial ties between health professionals and industry publicly transparent, has recently gone global. Given that transparency is not the sole means of managing conflict of interest, and is unlikely to be effective on its own, it is important to understand why disclosure has emerged as a predominant public policy solution, and what the effects of this focus on transparency might be. We used Carol Bacchi's problem-questioning approach to policy analysis to compare the Sunshine policies in three different jurisdictions, the United States, France and Australia. We found that transparency had emerged as a solution to several different problems including misuse of tax dollars, patient safety and public trust. Despite these differences in the origins of disclosure policies, all were underpinned by the questionable assumption that informed consumers could address conflicts of interest. We conclude that, while transparency reports have provided an unprecedented opportunity to understand the reach of industry within healthcare, policymakers should build upon these insights and begin to develop policy solutions that address systemic commercial influence.